The Perception by University Students of the Use Google Sites in The Chemistry Learning Media Course - Dira Ayu Annisa; Merlin Merlin; Linda Kurnia Mustafa; Hutri Handayani Isra (SAINTIFIK@: Jurnal Pendidikan MIPA, 2026)
ABSTRACT. Future teachers are expected to be proficient in utilizing technology in their learning, but media such as Google Sites are still underutilized by most teachers as learning resources or tools. This study aims to determine the perceptions of prospective teachers regarding the use of Google Sites in chemistry learning media courses. A descriptive approach using a survey method was chosen for this study, with two lecturers and 15 fifth-semester chemistry education students as subjects. The instrument used was a questionnaire consisting of closed-ended and open-ended questions. The results showed that both lecturers and students agreed to use Google Sites as a learning medium. In addition to being easy to access, this medium can be creatively added by adding materials, videos, animations, and so on as needed. The conclusion obtained is that students feel a positive impact after using Google Sites and this medium has the potential to be implemented in high schools/equivalents due to its easy access and attractive appearance.